Delay discounting behavior and white matter microstructure abnormalities in youth with a family history of alcoholism - Herting, Megan M. (2010)
BACKGROUND: Youth with family history of alcohol abuse have a greater risk of developing an alcohol use disorder (AUD). Brain and behavior differences may underlie this increased vulnerability. The current study examined delay discounting behavior and white matter microstructure in youth at high-risk for alcohol abuse, as determined by a family history of alcoholism (FH+), and youth without such family history (FH−). METHODS: Thirty-three healthy youth (FH+ = 15, FH− = 18), ages 11 to 15 years, completed a delay discounting task and underwent diffusion tensor imaging (DTI). Tract Based Spatial Statistics (Smith et al., 2006), as well as follow-up region-of-interest analyses, were performed in order to compare fractional anisotropy (FA) between FH+ and FH− youth. RESULTS: FH+ youth showed a trend toward increased discounting behavior and had significantly slower reaction times on the delay discounting paradigm compared to FH− youth. Group differences in FA were seen in several white matter tracts. Furthermore, lower FA in the left inferior longitudinal fasciculus and the right optic radiation statistically mediated the relationship between FH status and slower reaction times on the delay discounting task. CONCLUSION: Youth with a family history of substance abuse have disrupted white matter microstructure, which likely contributes to less efficient cortical processing, and may act as an intrinsic risk-factor contributing to an increased susceptibility of developing AUD. In addition, FHP youth showed a trend toward greater impulsive decision making, possibly representing an inherent personal characteristic that may facilitate substance use onset and abuse in high-risk youth.